2009
DOI: 10.1185/03007990903282297
|View full text |Cite
|
Sign up to set email alerts
|

Management of neuropathic pain after surgical and non-surgical trauma with lidocaine 5% patches: study of 40 consecutive cases

Abstract: Lidocaine 5% patches seem to be an effective treatment of post-surgical and post-traumatic pain. These results should be supported with randomised and placebo-controlled studies with larger sample sizes and longer follow-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 46 publications
3
33
1
3
Order By: Relevance
“…Nearly 75% of treatment effects occurred during the first five treatment weeks but ongoing plaster administration provided sustained pain relief and amelioration of pain-related impairments during the entire observation period of up to 12 weeks. These patient-reported clinical practice data confirm the efficacy of the plaster shown for PHN and other neuropathic conditions in previous studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . The mean 5-point reduction in average pain intensity shown over the treatment period of 12 weeks compares well with the 2.5-point improvement observed in a large comparative study after 4 weeks in PHN and DPN patients with the same mean baseline pain intensity (6.9 points, NRS averaged over the three previous days) 13 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nearly 75% of treatment effects occurred during the first five treatment weeks but ongoing plaster administration provided sustained pain relief and amelioration of pain-related impairments during the entire observation period of up to 12 weeks. These patient-reported clinical practice data confirm the efficacy of the plaster shown for PHN and other neuropathic conditions in previous studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . The mean 5-point reduction in average pain intensity shown over the treatment period of 12 weeks compares well with the 2.5-point improvement observed in a large comparative study after 4 weeks in PHN and DPN patients with the same mean baseline pain intensity (6.9 points, NRS averaged over the three previous days) 13 .…”
Section: Discussionsupporting
confidence: 89%
“…Efficacy, tolerability, and safety of the plaster have been established for postherpetic neuralgia (PHN) in a number of randomised clinical studies [11][12][13][14][15] . Beneficial effects have also been demonstrated for other neuropathic pain states 13,[16][17][18][19][20] . Pain relief was observed for up to seven treatment years with daily plaster use [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 90%
“…7,8 In randomized studies, lidocaine patches were effective in patients with postherpetic neuralgia, 7 and open-label studies have suggested efficacy in other neuropathic pain conditions. 9 An analgesic effect of lidocaine patches in persistent postsurgical pain has been suggested, 10,11 but randomized controlled studies are lacking.…”
Section: Pain Medicinementioning
confidence: 99%
“…Significant correspondence decreases in both pain intensity and LANSS score following treatment, as compared to no treatment, have been reported (36)(37)(38). In the present study, the LANSS Pain Scale was used for follow-up assessment of the treatment of NP; five patients in each group had a LANSS score <12 after one week of treatment and after one month of treatment; the reduction rate in the number of patients with NP was 33 percent.…”
Section: Discussionmentioning
confidence: 87%